The Cultural Differences influences on Knowledge Sharing Activities in Construction Project Collaboration - Tri Joko Wahyu Adi; Atif Musbah (IPTEK Journal of Proceedings Series, 2017)
In the last decades construction activity has been heavily criticized for its productivity and performance in relation to cultural differences. There have been several studies indicated that the cultural diversity influence the knowledge of the organization, and that result in barriers in knowledge sharing in the multicultural organization. The knowledge spreading manners affected by the cultural in organization due to ethnic, cities, sexual category, local culture, which that might lower level of the knowledge spreading in organization . Therefore, a research study is developed in order to assess the influences of cultural differences on the activity of knowledge distribution in organization project and to determine of extend of the cultural differences to obstacle the individual to share their knowledge within the organization or with other members of the organization and how is that leads to decrease the project’s performance. For seeking to achieve the aims of the study a survey questionnaire was used to gather data. System dynamic simulation is utilized to interpret the collected data in order to achieve meaningful information. The results proven that cultural difference is one of the major problems that impact the project performance negatively in the construction industry since it is verified that the cultural difference impacts the knowledge flow among the employees in the construction project which that strongly affects the outcome of the projects and that also leads to decrease the productivity of the project. In addition, the respondents also agree that cultural differences cause unsuccessful safety system in the construction projects. Therefore, the cultural differences should be given careful attention to ensure better project performance.